2019
DOI: 10.1186/s12884-019-2423-3
|View full text |Cite
|
Sign up to set email alerts
|

Weight retention at six weeks postpartum and the risk of gestational diabetes mellitus in a second pregnancy

Abstract: Background Gestational diabetes mellitus (GDM) is a common cause of maternal morbidity, and can lead to the development of diabetes later in life. Pre-pregnancy body weight is associated with the change in body mass index (BMI) between a first and second pregnancy. Compared with long-term change in BMI between pregnancies, the most accessible follow-up point to investigate BMI change is 6 weeks after the initial pregnancy. The present study aimed to assess the association between weight retention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 33 publications
(39 reference statements)
1
24
0
1
Order By: Relevance
“…Soria-Contreras et al found that postpartum weight retention and weight gain during the first year were positively correlated to HOMA-IR at six years postpartum. Another study found that women who gained excess weight from pregnancy to postpartum had a higher risk of gestational diabetes in subsequent pregnancies, 33 which suggests weight retained after pregnancy is intricately connected to insulin resistance during the months and even years after delivery. Taken together, the relationship noted in the present study may persist well beyond 6-months postpartum and potentially predispose mothers for gestational diabetes and type II diabetes development later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Soria-Contreras et al found that postpartum weight retention and weight gain during the first year were positively correlated to HOMA-IR at six years postpartum. Another study found that women who gained excess weight from pregnancy to postpartum had a higher risk of gestational diabetes in subsequent pregnancies, 33 which suggests weight retained after pregnancy is intricately connected to insulin resistance during the months and even years after delivery. Taken together, the relationship noted in the present study may persist well beyond 6-months postpartum and potentially predispose mothers for gestational diabetes and type II diabetes development later in life.…”
Section: Discussionmentioning
confidence: 99%
“…A range of anthropometric parameters were measured for each participant, including weight, height, heart rate, systolic blood pressure, and diastolic blood pressure; we also calculated the BMI [10]. At each visit, we also recorded the family history of diabetes as a parent or sibling may have been diagnosed as having diabetes in the interval since the previous visit [11].…”
Section: Data Collection Between 16 Weeks + 0 Days and 19 Weeks + 6 Daysmentioning
confidence: 99%
“…However, it is meaningless to inform a woman with these factors that she has an increased risk of GDM when she has already become pregnant again; physicians need to identify women with a high risk of GDM and implement primary prevention strategies before that point. Recently, Liu et al reported that the findings of their retrospective cohort study suggest that excessive postpartum weight retention (PPWR) six weeks after the first pregnancy is a risk factor for GDM in the second pregnancy [8]. Their study is different than previous investigations in proposing that the postpartum checkup might provide the opportunity to identify factors that increase the risk of GDM in a subsequent pregnancy, allowing the implementation of primary prevention strategies.…”
Section: Introductionmentioning
confidence: 97%
“…Research estimates indicate that GDM affects approximately 7-10% of all pregnancies worldwide [3][4][5][6]. GDM presents significant risks to the fetus, including an increased risk of macrosomia, neonatal hypoglycemia, hyperbilirubinemia, shoulder dystocia, and birth trauma [7,8]. Further, previous studies demonstrated that women with GDM have an increased risk of hypertensive disorders of pregnancy [9,10] and metabolic syndrome, type 2 diabetes mellitus, and cardiovascular disease later in life [11,12].…”
Section: Introductionmentioning
confidence: 99%